Relationship Between Learning Strategies with Children's Learning Motivation at Perguruan Pencak Silat Silutarrahmi, Kelurahan Kalumbuk, Kuranji Sub-District, Padang City - Jeni Febriani; Setiawati Setiawati (Universitas Negeri Padang, 2022)
This study is motivated by low motivation to learn of children at the silaturrahmi pencak silat college, Kalumbuk sub-district, Kuranji district, Padang city, which is suspected to have something to do with learning strategies. The purpose of this study is to reveal an overview of learning strategies, learning motivation of children at the silaturrahmi pencak silat school, Kalumbuk sub-district, Kuranji sub-district, Padang city, and to reveal the relationship between learning strategies and children's learning motivation at the silaturrahmi pencak silat school in Kalumbuk sub-district, Kuranji district, Padang city. This type of study is a descriptive correlation study with a quantitative approach. The subjects of this survey were 84 students enrolled in Pencak Silat Silaturrahmi School in 2020, 51 using a 60% sample, or stratified random sampling method. The data collection method used is a survey and the tool used is a questionnaire. Data analysis techniques use percentage and product moment formulas. The results of this study show that: 1) the learning motivation of children at the silaturrahmi pencak silat college, Kalumbuk sub-district, Kuranji sub-district, Padang city is low; 2) learning strategies at the pencak silat school of silaturrahmi, Kalumbuk sub-district, Kuranji sub-district, Padang city are classified as low; 3) there is a significant relationship between learning strategies and children's learning motivation at the silaturrahmi pencak silat college, Kalumbuk sub-district, Kuranji sub-district, Padang city. The suggestion of this research is that it is hoped that the manager of the pencak silat silaturrahmi college in Kalumbuk sub-district, Kuranji district, Padang city can encourage educators to make interesting learning strategies for students in order to achieve learning objectives.